2019
DOI: 10.4103/ijo.ijo_1378_18
|View full text |Cite
|
Sign up to set email alerts
|

Macular ganglion cell complex parameters by optical coherence tomography in cases of multiple sclerosis without optic neuritis compared to healthy eyes

Abstract: Purpose: To compare different macular thickness parameters and peripapillary retinal nerve fiber layer (RNFL) thickness between recently diagnosed cases of multiple sclerosis (MS) without optic neuropathy (ON) and healthy individuals. Methods: This cross-sectional study was performed between June 2014 and June 2015. All subjects underwent ocular and retinal examination. Spectral domain optical coherence tomography (SD-OCT) was used to measure the thickness of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The observed dissociation between changes in pRNFL thickness and other OCT parameters in MS patients may at least partially explain the results of our study. Support for this concept also comes from a study performed by Lotfy et al [64], who found lower macular RNFL thickness in MS patients without ON compared with healthy controls, and no differences in pRNFL thickness between the two groups. Based on published results that show a better correlation of visual function and disability in MS patients and macular ganglion cell layer thickness than pRNFL [68], we can assume that in our MS patients, axonal degeneration may be more pronounced than in NSWMLs patients, and that the measurement of GCIPL and mRNFL thickness is more reliable than pRNFL in the differential diagnosis of MS.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The observed dissociation between changes in pRNFL thickness and other OCT parameters in MS patients may at least partially explain the results of our study. Support for this concept also comes from a study performed by Lotfy et al [64], who found lower macular RNFL thickness in MS patients without ON compared with healthy controls, and no differences in pRNFL thickness between the two groups. Based on published results that show a better correlation of visual function and disability in MS patients and macular ganglion cell layer thickness than pRNFL [68], we can assume that in our MS patients, axonal degeneration may be more pronounced than in NSWMLs patients, and that the measurement of GCIPL and mRNFL thickness is more reliable than pRNFL in the differential diagnosis of MS.…”
Section: Discussionmentioning
confidence: 79%
“…Surprisingly, we did not observe any differences in segmental and average thickness of the pRNFL between MS and NSWMLs patients. Thinning of the pRNFL has been observed in MS-ON and also in MS-NON eyes [39,60,63,64]. However, some results did not confirm these observations [39,[64][65][66][67].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been demonstrated in the literature that RNFL in patients with early-diagnosed MS NON was no different than that of control subjects in 4 quadrants; however, there was signi cant thinning in MS NON patients in GCC. Based on these ndings, it can be speculated that patients with early-diagnosed MS present GCC symptoms earlier than RNFL symptoms [15]. Similarly, a meta-analysis reported that the ganglion cell layer was signi cantly thinner in the MS ON and MS NON groups compared to the control group and that the inner plexiform layer was signi cantly thinner in the ganglion cell inner plexiform layer MS ON group compared to the MS NON group [17].…”
Section: Discussionmentioning
confidence: 95%
“…examined regions (macula, ganglion cell complex, and RNF). In glaucoma patients the ganglion cell complex in the inferior temporal outer sector was reported to be the most useful variable (area under the ROC curve 0.86; [6]). Loss of ganglion cells may be simpler to detect than that in the peripheral retina due to the multilayer structure of these cells' bodies.…”
Section: Introductionmentioning
confidence: 99%